Survey on Development Pattern of Women's Futsal Club in Kebumen Regency - Ibnu Prasetyo Widiyono; Agus Setiandi; Ari Susanto (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Futsal which is played by women is currently a sport that is quite popular in Indonesia and is in great demand by the public. This study aims to determine the development problems of the women's futsal club in Kebumen Regency and provide training programs that are in accordance with the training program as the basis for futsal coaching. This research is quantitative and descriptive. The data collection technique used in this research is a survey method with research questionnaires in the form of questions related to one topic or one related topic, which must be answered by the subject. The results of the study revealed that if the development of the women's futsal club in Kebumen Regency was a good category, the facilities and infrastructure of the women's futsal club in Kebumen Regency were in a good category, and the organization of the women's futsal club in Kebumen Regency was well organized, most of the coaches of the women's futsal club in Kebumen already had certified coach and in terms of funding the futsal club in Kebumen is a good category. Keywords: Facilities, Futsal, Infrastructure, Kebumen, Women